2022
DOI: 10.1155/2022/3881962
|View full text |Cite
|
Sign up to set email alerts
|

Effects on Autophagy of Moxibustion at Governor Vessel Acupoints in APP/PS1double-Transgenic Alzheimer’s Disease Mice through the lncRNA Six3os1/miR-511-3p/AKT3 Molecular Axis

Abstract: Objective. To explore the effect and mechanism of moxibustion at acupoints of the governor vessel on lncRNA Six3os1 in amyloid precursor protein/presenilin1 (APP/PS1) double-transgenic Alzheimer’s disease (AD) mice. Methods. Twenty-four specific pathogen-free and APP/PS1 double-transgenic male mice were randomly allocated into the AD model and moxibustion groups, with 12 cases in each group. Twelve syngeneic C57BL/6J mice were selected as the control group. Mice in the moxibustion group received aconite cake-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…[ 32 ] As a key regulator of energy metabolism, PPARA regulates mitochondrial and peroxisome functions. [ 33 ] Activation of PPARA can reverse normal autophagy inhibition, induce autophagy lipid degradation, [ 34 ] and mediate host innate defense. [ 35 ] PPARA gene variations have been found to be associated with AD.…”
Section: Discussionmentioning
confidence: 99%
“…[ 32 ] As a key regulator of energy metabolism, PPARA regulates mitochondrial and peroxisome functions. [ 33 ] Activation of PPARA can reverse normal autophagy inhibition, induce autophagy lipid degradation, [ 34 ] and mediate host innate defense. [ 35 ] PPARA gene variations have been found to be associated with AD.…”
Section: Discussionmentioning
confidence: 99%
“…The knockdown of MIR600HG markedly ameliorated the cognitive impairment in AD mice [58]. Interestingly, Jia et al reported that moxibustion can inhibit the expression of lncRNA SIX3OS1 in AD mice; silencing SIX3OS1 promoted autophagy and accelerated Aβ1-42 clearance by inactivating PI3K/AKT/mTOR signaling [62].…”
Section: Lncrnas Regulate Alzheimer's Disease By Modulating Autophagymentioning
confidence: 99%
“…With the development of new RNA-based therapeutic strategies, we believe that lncRNA could be a therapeutic treasure for NDDs. Inhibit Promote NEAT1 [120] MIR600HG [58] SIX3OS1 [62] RMRP [59] Activate Promote BACE1-AS [60] LINC-01311 [61] Inhibit Suppress…”
Section: Targeting Autophagy-related Lncrnas As a Therapeutic Strateg...mentioning
confidence: 99%
“…This suggests that moxibustion can improve autophagy function and eliminate Aβ protein deposition in the brain of AD rats by regulating the PI3 K/Akt/mTOR and mTOR/ p70S6K signaling pathways. [17][18][19][20] Furthermore, moxibustion may also inhibit autophagy by inhibiting the mTOR/ TFEB signaling pathway. 21 Overall, mTOR functions as a central integrator of various signaling pathways.…”
Section: Signaling Pathways Activated By Acupuncture That Interfere W...mentioning
confidence: 99%